Implications of CLEC3B as a Prognostic Marker in Oral Squamous Cell Carcinoma - Zehra Ahmed; Fouzia Shaikh; Shumaila Usman; Akhtar Ali; Haroon Rasheed; Asma Akram (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: To examine the prognostic significance of C-Type Lectin Domain Family 3 Member B (CLEC3B) and Tetranect in in Oral squamous cell carcinoma (OSCC). Methods: A case-control study was conducted on saliva samples of 60 participants including 20 OSCC, 20 Postoperative OSCC, and 20 healthy individuals, to determine the salivary expression of CLEC3B in OSCC. Regarding the inclusion criteria, OSCC patients diagnosed based on histopatho- logical examination were included in the OSCC group. Patients diagnosed with oral premalignant lesions and conditions on the basis of histopathological examination were included in the Oculopharyngeal Muscular Dystrophy (OPMD) group. In the Persistent Suspicious Oral Mucosal lesions (PSOML) group, patients with any suspicious oral lesion based on clinical assessment were included. Controls were healthy individuals and none of the patients received any surgery other than biopsy. Regarding the exclusion criteria, patients having malignancies other than OSCC were excluded. Patients having a history of autoimmune diseases or HIV infection were also excluded from the study. All samples were collected from Abbasi Shaheed Hospital and Ziauddin University Hospital. Written informed consent was obtained before taking samples. mRNA levels were detected through RT-qPCR and Tetranectin levels were identified by ELISA. Results: CLEC3B was Significantly expressed in OSCC, postoperative patients, and healthy individuals (p-value 0.019). It was significantly down regulated in OSCC compared with controls (p-value 0.014) whereas no significance was found in mRNA levels of OSCC and Postoperative OSCC cases. Tetranectin expression was significantly down regulated in OSCC compared with postoperative OSCC and controls (p-value 0.03). Conclusion: These results indicated that CLEC3B and Tetranectin have the potential to serve as prognostic biomarkers for OSCC as it is significantly decreased in OSCC. Decreased expression of CLE- C3B and Tetranectin with the progression of cancer staging and grading, suggests its tumor suppressive function. Moreover, the utilization of saliva as a noninvasive method for detecting biomarkers adds to the feasibility and relevance of these findings.